L-glutamina + L-ácido glutâmico em dietas contendo ou não produto lácteo para leitões desmamados - Almeida, Jonathan Mádson dos Santos (2018)
The objective of this work was to evaluate the supplementation of L-glutamine + L- glutamic acid in diets containing or not dairy products for weaned piglets on the performance, incidence of diarrhea, organ weight, morphometry and intestinal health, measurement of hepatic glycogen and economic viability. For this purpose, 40 piglets were used, with initial mean weight of 6.6 ± 0.6 kg, being 20 castrated males and 20 females of the same commercial strain. The animals were distributed in a randomized block design with four treatments, consisting of: DSL- Diet with corn and soybean meal; DSLG - Diet with corn, soybean meal, supplemented with 1% L-glutamine + L-glutamic acid; DCL - Diet with corn, soybean meal and dairy product; DCLG - Diet with corn, soybean meal, dairy product and addition of 1% of L-glutamine + L-glutamic acid, with five replicates and two animals per experimental unit. The following periods were analyzed: I- 24 to 35 days, II- 24 to 42 days and III- to 24 to 55 days of age. The supplementation of L-glutamine associated with L-glutamic acid in diets with or without dairy product improved (P <0.05) the variables final weight, daily gain and feed conversion in the three periods analyzed (I, II and III) . There was no influence of the experimental diets on the incidence of diarrhea nor on the relative weight of the liver, spleen and pancreas. The exclusively vegetal diet (DSL) worsened (P <0.05) the height of the villi, depth of the crypts, villi width and goblet cells of the duodenum, and crypt depth, villus width, absorptive area and jejunum goblet cells, possibly due to the influence of the higher apoptosis rate (P <0.05) observed in the duodenum Animals that consumed the diet supplemented with L-glutamine + L-glutamic acid (DSLG) had a higher rate of cellular mitosis (P <0.05) in the duodenum and jejunal epithelium when compared to the animals that consumed the amino acid addition diet the dairy product (DCLG). Regarding the measurement of hepatic glycogen, it was observed that the addition of L-glutamine + L-glutamic acid and dairy product (DCLG) improved (P <0.05) glycogen deposition. The inclusion of L-glutamine + L-glutamic acid in exclusively vegetable diets is economically more viable (P <0.05) than diets containing dairy product or association of the dairy product and L-glutamine + L-acid glutamic acid. It is recommended to supplement 1% and L-glutamine + L-glutamic acid in diets without dairy product, as it improves the productive parameters and related to intestinal integrity, besides being economically viable.